Crimes affecting state security : problems and recent trends - Sinha, Rajeev Kumar (New Delhi : Deep & Deep Publications, 1995)
With special reference to India.
Includes bibliographical references (p. [368]-372) and index.
Keywords: Terrorism -- India; Espionage -- India -- History; National security -- India